Cerosomes as skin repairing agent: Mode of action studies with a model stratum corneum layer at liquid/air and liquid/solid interfaces - Strati, Fabio; Mukhina, Tetiana; Neubert, Reinhard H H; Opalka, Lukas; Hause, Gerd; Schmelzer, Christian E H; Menzel, Matthias; Brezesinski, Gerald (BBA advances, 2022)
The stratum corneum (SC) is the largest physical barrier of the human body. It protects against physical, chemical and biological damages, and avoids evaporation of water from the deepest skin layers. For its correct functioning, the homeostasis of the SC lipid matrix is fundamental. An alteration of the lipid matrix composition and in particular of its ceramide (CER) fraction can lead to the development of pathologies such as atopic dermatitis and psoriasis. Different studies showed that the direct replenishment of SC lipids on damaged skin had positive effects on the recovery of its barrier properties. In this work, cerosomes, i.e. liposomes composed of SC lipids, have been successfully prepared in order to investigate the mechanism of interaction with a model SC lipid matrix. The cerosomes contain CER[NP], D-CER[AP], stearic acid and cholesterol. In addition, hydrogenated soybean phospholipids have been added to one of the formulations leading to an increased stability at neutral pH. For the mode of action studies, monolayer models at the air-water interface and on solid support have been deployed. The results indicated that a strong interaction occurred between SC monolayers and the cerosomes. Since both systems were negatively charged, the driving force for the interaction must be based on the ability of CERs head groups to establish intermolecular hydrogen bonding networks that energetically prevailed against the electrostatic repulsion. This work proved for the first time the mode of action by which cerosomes exploit their function as skin barrier repairing agents on the SC.
Keywords: Hydrogen bonding network; Skin barrier repairing agents; Ceramides; Stratum corneum; Liposomes; Langmuir monolayer